Strategies and Challenges for Distributing Leadership in Communities of Practice. Issue 4 (April 2017) - Lester, Jaime; Kezar, Adrianne
Abstract : A major concern of higher education in the United States and abroad is increasing the number of college‐educated citizens in science, technology, engineering, and mathematics (STEM) fields. Researchers argue that innovative and empirically tested teaching practices will support STEM college student retention and degree completion. Promoting change in pedagogy reform among faculty is found to be successful in communities of practice (CoP) where individuals come together based on a common interest or passion in a distributed leadership model. In the CoP and distributed leadership literature, leadership is process oriented, shared, situated, and dependent on a positional or key leader, termed the community coordinator. What is not present in the literature is how a community, such as a CoP, manages to continue a distributed leadership model during critical leadership junctures. Drawing on interviews of over 112 individuals, three key themes were identified related to strategies leadership development and challenges for distributing leadership in CoPs beyond the core group. The findings identify the need for a new CoP leadership model that engages the multiple levels of CoP membership in the earlier stages of formation.